Application of synthetic and grafted polymeric flocculants in agricultural wastewater treatment - Mohamed N Ali; Mohammed S Fahmy; Rehab M Elhefny (Journal of Degraded and Mining Lands Management, 2021)
Due to the large amounts of freshwater consumed in Egypt by the agricultural sector that is more than 85% of Egypt share of freshwater in addition to the high concentrations of salts, chemicals and nutrients produced from fertilizers. Reduction of these pollutants concentrations to an acceptable level and breaking the sedimentation stability of colloidal substances and organic particles for reuse for irrigation purposes was associated with the application of biological treatment with coagulants addition. The flocculation process was performed by using polydiallyldimethylammonium chloride (polyDADMAC) and polyacrylamide grafted oatmeal (OAT-g-PAM). The scale-pilot consists of an aeration tank equipped with an air blower, sedimentation tank followed by a filtration stage through 20 cm of pottery scrubs media. To study the performance of synthetic and grafted polymeric flocculants, 3 trials were performed. Activated sludge process without adding any polymeric flocculants was the control trial. In the second trial, polyDADMAC was added with a dose of 5 mg/l. Finally, OAT-g-PAM with a dose of 1.25 mg/l was used in the third trial. The physicochemical properties of agricultural wastewater were measured at the national research center in Cairo. It was found that OAT-g-PAM incorporated with activated sludge process was the most effective in treating agricultural wastewater as it achieved COD, BOD,TKN, TP, and TSS removal efficiency up to 92.29%, 93.13%, 90.64%, 90.46%, and 92.5%, respectively which made it suitable to reuse for agricultural purposes, in addition to its ability to biodegrade, environmentally friendly, and low dosage required compared to polyDADMAC.